2022
DOI: 10.3389/fpubh.2022.941206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of COVID-19 Vaccine Acceptance Among Healthcare Workers: A Systematic Review

Abstract: COVID-19 is a major public health problem that has been seriously affecting the global community. Healthcare workers (HCWs) are at high risk of infection due to being directly involved in diagnosing and taking care of patients. Due to this, they were prioritized to receive the initial supply of vaccines. However, vaccine hesitancy has been identified as a major global public health threat. Therefore, this review aimed to synthesize pieces of evidence on the prevalence of COVID-19 vaccine acceptance and determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 59 publications
(175 reference statements)
4
27
0
Order By: Relevance
“…In a recent metanalysis, Wang and colleagues found that the global pooled acceptance rate of COVID-19 vaccination was 67.8% (95% CI: 67.1–68.6) among the general population, and 67.5% (95% CI: 64.4–70.6) among HCWs [ 7 ]. For example, recently, a systematic review reported that vaccine acceptance amongst HCWs correlated with their willingness to recommend the COVID-19 vaccination to their patients [ 8 ]. In this sense, it is necessary to investigate HCWs’ COVID-19 vaccine hesitancy to better understand the barriers, especially considering the last WHO’s global COVID-19 vaccination strategy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent metanalysis, Wang and colleagues found that the global pooled acceptance rate of COVID-19 vaccination was 67.8% (95% CI: 67.1–68.6) among the general population, and 67.5% (95% CI: 64.4–70.6) among HCWs [ 7 ]. For example, recently, a systematic review reported that vaccine acceptance amongst HCWs correlated with their willingness to recommend the COVID-19 vaccination to their patients [ 8 ]. In this sense, it is necessary to investigate HCWs’ COVID-19 vaccine hesitancy to better understand the barriers, especially considering the last WHO’s global COVID-19 vaccination strategy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews and meta-analyses investigated intention of HCWs to accept a COVID-19 vaccine [ 21 , 22 , 23 , 24 , 25 ]. Evidence shows that the main predictors for COVID-19 vaccine acceptance among HCWs are male gender, older age, and previous influenza vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Hesitancy against vaccines is common in public and among healthcare workers, with post-vaccination side effects being the key barrier [ 57 ]. Open discussion about the possible side effects and reinforcing the individual, family, and community benefits are key to promoting acceptance [ 58 ]. Addressing the unique barriers to vaccine acceptance based on community dynamics, sociocultural factors, and vaccine criticism while providing well-informed messaging is vital [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%